Burden of bacterial meningitis in India: Preliminary data from a hospital based sentinel surveillance network - Jayaraman, Yuvaraj; Veeraraghavan, Balaji; Chethrapilly Purushothaman, Girish Kumar; Sukumar, Bharathy; Kangusamy, Boopathi; Nair Kapoor, Ambujam; Gupta, Nivedita; Mehendale, Sanjay Madhav (PloS one, 2018)
Worldwide, acute bacterial meningitis is a major cause of high morbidity and mortality among under five children, particularly in settings where vaccination for H. influenzae type b, S. pneumoniae and N. meningitidis is yet to be introduced in the national immunization programs. Estimation of disease burden of bacterial meningitis associated with these pathogens can guide the policy makers to consider inclusion of these newer vaccines in the immunization programs. A network of hospital based sentinel surveillance was established to generate baseline data on the burden of bacterial meningitis among children aged less than 5 years in India and to provide a platform for impact assessment following introduction of the Pentavalent and Pneumococcal Conjugate Vaccines (PCV). During surveillance carried out in select hospitals across India in 2012-2013, information regarding demographics, immunization history, clinical history, treatment details and laboratory investigations viz. CSF biochemistry, culture, latex agglutination and PCR was collected from children aged 1 to 59 months admitted with suspected bacterial meningitis. A total of 3104 suspected meningitis cases were enrolled from 19,670 children admitted with fever at the surveillance hospitals. Of these, 257 cases were confirmed as cases of meningitis. They were due to S. pneumoniae (82.9%), H. influenzae type b (14.4%) and N. meningitidis (2.7%). Highest prevalence (55.3%) was observed among children 1 to 11 months. Antimicrobial susceptibility testing revealed considerable resistance among S. pneumoniae isolates against commonly used antibiotics such as cotrimoxazole, erythromycin, penicillin, and cefotaxime. More commonly prevalent serotypes of S. pneumoniae in circulation included 6B, 14, 6A and 19F. More than 90% of serotypes identified were covered by Pneumococcal Conjugate Vaccine 13. We observed that S. pneumoniae was the commonest cause of bacterial meningitis in hospitalized children under five years of age in India. Continued surveillance is expected to provide valuable information and trends in future, to take an informed decision on introduction of pneumococcal vaccination in Universal Immunization Programme in India and will also eventually help in post-vaccination impact evaluation.